An Analysis of Effective School Characteristics Practices in Schools - Syahputra, Syarif Faldy; Irwan, Dedi; Sahrawi, Sahrawi; Putra, Muhammad Iqbal Ripo (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
The main objective of this research is to describe the intensity of the related variables practices and its variations that occurred. This research uses quantitative approach with survey research method. The subject of this research was 26 schools in 8 regencies of West Kalimantan. In the process of data collection, researcher used a close-ended questionnaire and the obtained data were analyzed by using descriptive statistics and inferential statistics technique. Researcher also uses Microsoft Excel Software and SPSS 26 in processing and analyzing the obtained data. The findings indicated that the practices of the Learning Environment and Learning Organization variables were frequently implemented in most schools, reflecting a focus on school effectiveness. However, the Home-School Partnership variable was less frequently practiced, suggesting that schools faced challenges in achieving school effectiveness in this aspect. Researcher found the variations that occurred based on the region of origin and school levels.